Comparative study of conventional exfoliative cytology and centrifuged liquid-based cytology in oral leukoplakia and oral squamous cell carcinoma patients - R. Jayabalan; Ambika Murugesan; Sekar Balakrishnan; Maya Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: This study aims to compare the efficacy between conventional exfoliative cytology (EC) and centrifuged liquid-based cytology (CLBC) in control, leukoplakia, and oral squamous cell carcinoma (OSCC) patients. Oral leukoplakia and oral cancer require an early definitive diagnosis for better prognostic outcome. Oral EC, a minimally invasive technique that involves the examination of desquamated cells from the tissue surfaces used as a method of early diagnosis. CLBC is a modified technique that is used to achieve improved quality of the cytology findings. Materials and Methods: A comparative study was done in 30 subjects, of which, 10 cases from control group, 10 oral leukoplakia, and 10 OSCC cases. These subjects were selected according to the appropriate inclusion and exclusion criteria. The cases in each group underwent conventional as well as CLBC. The comparison was carried out between these groups with respect to the cellular and background stromal factors. Appropriate qualitative evaluation of the samples was collected and statistical analysis was done using the Chi-squared test. The significance level of value was P < 0.05. Results: Significant results were obtained for certain parameters such as cellular overlap clear background, uniform distribution in control, leukoplakia, and OSCC with a P = 0.004**, P = 0.001**, P = 0.006** using CLBC. Conclusion: CLBC is better and give clearer vision as compared to conventional cytology and can be used in the early diagnosis.